The Importance of Housing Policy in Uzbekistan in Connection with Innovative Economy - Yuldosheva Shakhribonu Anvarqizi (International Journal on Economics, Finance and Sustainable Development, 2022)
In this article, we have described the housing policy, housing and communal services activities, types of services, ongoing reforms to improve the efficiency of housing and communal services and their main directions.